(untitled) (Bangladesh Journal of Infectious Diseases, 2025)
A parasitic skin illness, scabies disproportionately affects underprivileged population. Significant morbidity is brought on by the illness, which also includes immune-mediated illness and serious bacterial infections. Sarcoptes scabiei is an obligatory parasite of human skin, is the cause of the infectious illness scabies. People of all ages, genders, and socioeconomic backgrounds are impacted by the disease. Direct contact with an infected individuals and personal objects like clothing and bed linens are the primary ways that the infection is spread. The etiology of scabies in Bangladesh is linked to environmental pollution, poor living conditions, personal hygiene, water sanitation, and socioeconomic profile. Thus, the goal of this review was to represent the prevalence of scabies, its contributing causes, illness characteristics, diagnosis and management, and other relevant things. Bangladesh Journal of Infectious Diseases, June 2025;12(1):151-158